Diseño de un plan de marketing social como estrategia de ventaja competitiva para la empresa Direct Flowerex Ecuador S.A. - Viscaíno Marcillo, Amanda Gabriela (2015)
This research aims to design a social marketing plan and strategy of competitive advantage for the company Direct Flowerex Ecuador. SA, using social marketing tool for the dissemination of social programs developed by the company. Direct Flowerex Ecuador SA is a company dedicated to the marketing of fresh flowers to the United States, and looks at the need to develop a strategy of competitive advantage that distinguishes you from other brokers; within their core business strategies are not developed social marketing, so that the activities of contribution to the community that has made have been sporadic and without a definite plan. That is why the use of social marketing as a tool for competitive advantage arises because it facilitates a defined social plans that the company wants routing, generating greater commitment to society yet, be entrepreneurially more competitive. For the realization of social programs a strategic alliance with the Ecuadorian General Foundation in Sangolquí, dedicated to training and social inclusion for people with intellectual disability arises; through the creation of a florist department, according to Ecuadorian roses that certain quality standards are intended for domestic consumption. In this way the company wants to contribute a vulnerable sector of society while improving their corporate image in the national and international market.